Internet of Things (IoT) Innovation and Application to Intelligent Governance Systems: A Case Study on DISHUB for Transport Vehicles - Abdul Azis; Dwi Krisbiantoro; Riyanto - (Society of Visual Informatics, 2023)
Vehicles can be used to facilitate humans in carrying out their daily activities. Motorized vehicles are divided into 3: land, sea, and air. Apart from the many benefits that can be obtained, motorized vehicles have dangers related to high-risk accidents. The highest cause of motorized vehicle accidents on land is road damage due to overload vehicles. Brake failure due to overload vehicles also contributes to vehicle accidents. This research aims to create an Internet of Things (IoT) based application to detect motorized vehicle load conditions. It was combined with several other technologies to produce a tool for detecting motor vehicle load conditions. The Extreme Programming Method is being used in this research. The Extreme Programming method is considered more suitable for completing this research because the communication with stakeholders is quite different. The Extreme Programming Method enables it to go back to the next step if discrepancies are encountered in making the system. The result of this research is an IoT-based tool called e-overload. It can detect vehicle loads, provide information for the drivers, and inform the results to related officers at the same time. E-overload tool will enable the drivers to get real-time information on the load on their vehicles. Officers will get additional evidence and the latest position of the vehicle to carry out actions against motorists who operate their vehicles with excessive loads.